Bridging the Gap between Tax Knowledge and Tax Clearance: A Study of Public Campus Faculties in Nepal - Budhathoki, Dhiraj (KMC Research Journal, 2025)
This research article, entitled 'Bridging the Gap between Tax Knowledge and Tax Clearance: A Study of Public Campus Faculties in Nepal,' explores the critical role of tax knowledge in influencing voluntary tax compliance among public campus faculties in Nepal. Drawing on the Theory of Planned Behavior, the study explored the extent of faculty understanding of the Nepali tax system and its impact on the acquisition of Tax Clearance Certificates (TCC). Using a quantitative approach with 400 public campus faculty members, the study shows a significant disparity between self-reported theoretical tax knowledge and practical application. While respondents exhibited moderate understanding of the tax system and laws (mean scores above 3.5), their practical application capability was notably weak (mean = 2.01). Chi-square analyses demonstrate that general tax knowledge does not significantly affect timely TCC acquisition, but knowledge of tax laws (p = 0.000), application skills (p = 0.002), and payment procedures (p = 0.000) are statistically significant predictors of compliance behavior. The study highlights structural gaps in tax education across disciplines and calls for practical, targeted educational activities. It recommends collaboration between the Inland Revenue Department (IRD) and academic institutions to deliver regular workshops and integrate applied tax education into faculty development programs. The findings affirm that improving procedural knowledge not just theoretical understanding is key to fostering a tax-compliant culture, particularly in a context of limited institutional trust and digital literacy.